Accountability in Public Policy Partnerships - Steets, J. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org. This book presents a new model of accountability which ensures that public-private partnerships don't erode public accountability. It defines concrete accountability standards for different types of partnerships.